Convergence of nanotechnology with radiation therapy—insights and implications for clinical translation - Chatterjee, Dev Kumar; Wolfe, Tatiana; Lee, Jihyoun; Brown, Aaron P; Singh, Pankaj Kumar; Bhattarai, Shanta Raj; Diagaradjane, Parmeswaran; Krishnan, Sunil (Translational Cancer Research; Vol 2, No 4 (August 26, 2013): Translational Cancer Research (Nanotechnology in Radiation Research), 2013)
Improvements in accuracy and efficacy in treating tumors with radiation therapy (RT) over the years have been fueled by parallel technological and conceptual advances in imaging and imageguidance techniques, radiation treatment machines, computational methods, and the understanding of the biology of tumor response to RT. Recent advances in our understanding of the hallmarks of cancer and the emergence of strategies to combat these traits of cancer have resulted in an expanding repertoire of targeted therapeutics, many of which can be exploited for enhancing the efficacy of RT. Complementing this advent of new treatment options is the evolution of our knowledge of the interaction between nanoscale materials and human tissues (nanomedicine). As with the changes in RT paradigms when the field has encountered newer and maturing disciplines, the incorporation of nanotechnology innovations into radiation oncology has the potential to refine or redefine its principles and revolutionize its practice. This review provides a summary of the principles, applications, challenges and outlook for the use of metallic nanoparticles in RT.